Pengaruh Mekanisme Good Corporate Governance (Gcg) Terhadap Kinerja Keuangan Perusahaan Sebelum Masa Pandemi Covid-19 - Khairunnisa; Besli, Eugenius (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2023)
This research was conducted to determine the effect of Good Corporate Governance (GCG) on company performance in manufacturing companies listed on the Indonesian stock exchange in 2017-2019. This study aims to determine the correlation that occurs between the independent variables and the dependent variable. The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX). The selection of the research sample used a purposive sampling method with a total of 183 companies registered. Good Corporate Governance (GCG) in this study is described by the variables of managerial ownership, institutional ownership, board of commissioners and audit committees, while company performance is described by Return On Assets (ROA). The data used in this study are annual reports issued by companies listed on the IDX website. Testing the data in this study using SPSS. The results of the study show that managerial ownership, institutional ownership, the board of commissioners and the audit committee have an influence on the company's financial performance. Keywords: Managerial Ownership, Institutional Ownership, Board of Commissioners, Audit Committee, and Return On Assets (ROA).